Pengaruh Likuiditas Dan Profitabilitas Terhadap Struktur Modal Pada Perusahaan Perbankan Di Bursa Efek Indonesia - Muhammad Rivandi; Novriani Novriani (JURNAL PUNDI, 2021)
Capital structure describes the company's permanent financing consisting of long-term debt and own capital. The purpose of this study is to obtain empirical evidence regarding the effect of liquidity and profitability on capital structure. The study population is all banking companies listed on the Indonesia Stock Exchange. The sample in this study was 37 banking companies selected using the purposive sampling method with 3 years of observation, namely 2016-2018. The analytical method used is the panel regression method. Based on the hypothesis the results of the study indicate that liquidity has a negative effect on capital structure, and profitability has a positive and significant effect on capital structure.  Keywords: liquidity and profitability, capital structure